الرواية العربية المعاصرة والثالوث المحرم ؛ الدين والسياسة والجنس - كنتاوي, محمد; عطية, نسرين (جامعة الوادي - university of Eloued, 2022)
يشكل الفن الروائي مكانة معتبرة في حياتنا الواقعية والفنية والجمالية، وقد بات من المؤكد في الوقت الحالي بأن الرواية العربية اختلفت عن سابقتها الكلاسيكية شكلا ومضمونا، ذلك لأنها تشبعت من مختلف الأنساق الجمالية والثقافية، كما أن الروائي المعاصر أشار الى قضايا تدل على عنايته بها كونها قضايا محظورة " الدين والسياسة والجنس"، والهدف من تناولنا لهذه الظاهرة ضمن هذا البحث هو الوقوف على توظيف هذا الثالوث المحرم في الإبداع الروائي المعاصر الذي خالف المألوف وأدخل الرواية عوالم التجديد، ووفق منهج استقرائي بآليتي الوصف والتحليل. Abstract: The art of Novels constitutes an important place in our real, artistic and aesthetic life. It is certain that the Arabic novel differed from its classical predecessor in terms of form and content due to the various aesthetic and cultural stiles. The contemporary novelist also referred to issues that indicate his care about them, as they are prohibited issues, “religion, politics, and gender.” The aim of studying this phenomenon within this paper is to identify the employment of this forbidden trinity in contemporary novelist creativity, which violated the norm and entered the novel into the worlds of renewal and this research is undertaken using an inductive approach employing two mechanisms of description and analysis.
مقال
Keywords: الرواية؛ المعاصرة؛ العربية؛ الدين؛ السياسة؛ الجنس; Contemporary Arabic Novel; Religion; Politics; Sex.